Detecting the retention potential of a reservoir influenced by upstream inputs from metropolitan areas - Silva, Fabio Leandro da; Fushita, Ângela Terumi; Cunha-Santino, Marcela Bianchessi da; Bianchini Júnior, Irineu (National Journal of City Management, 2026)
Objective – To evaluate the retention capacity of a hypereutrophic reservoir (Barra Bonita Reservoir – BBR, São Paulo State, Brazil), influenced by tributaries strongly impacted by anthropogenic activities in metropolitan regions.Methodology – Application of a zero-dimensional model using limnological data from 2010 to 2019, considering two upstream monitoring stations (Piracicaba and Tietê rivers) and one downstream station. The following water quality variables were analyzed: ammoniacal nitrogen, biochemical oxygen demand, dissolved oxygen, electrical conductivity, thermotolerant coliforms, total chloride, nitrate, nitrite, pH, total phosphorus, total solids, and turbidity. For each variable, retention capacity (alpha parameter) was assessed, resulting in 649 determinations. A Spearman correlation analysis (p-value: 0.05) was performed to explore relationships among reservoir physical characteristics, retention processes, and precipitation.Originality/Relevance – This study applies a zero-dimensional model to assess reservoir retention capacity while explicitly considering temporal variability.Results – Retention time ranged from 16 to 321 days, and the system exhibited a high retention capacity, as indicated by positive alpha coefficients for all analyzed variables.Theoretical/Methodological Contributions – The findings provide important support for advancing water management strategies and informing public policy formulation aimed at multiple water uses.Social and Environmental Contributions – Despite anthropogenic pressures, the BBR provides an essential ecosystem service by improving downstream water quality through the attenuation of pollutant loads.
Keywords: Ecosystem Goods; Man-made Lake; Mathematical Modeling